Insights Into Vascular Anomalies, Cancer, and Fibroproliferative Conditions: The Role of Stem Cells and the Renin-Angiotensin System - Kilmister, Ethan J.; Tan, Swee T. (Frontiers in Surgery, 2022)
Cells exhibiting embryonic stem cell (ESC) characteristics have been demonstrated in vascular anomalies (VAs), cancer, and fibroproliferative conditions, which are commonly managed by plastic surgeons and remain largely unsolved. The efficacy of the mTOR inhibitor sirolimus, and targeted therapies that block the Ras/BRAF/MEK/ERK1/2 and PI3KCA/AKT/mTOR pathways in many types of cancer and VAs, further supports the critical role of ESC-like cells in the pathogenesis of these conditions. ESC-like cells in VAs, cancer, and fibroproliferative conditions express components of the renin-angiotensin system (RAS) – a homeostatic endocrine signaling cascade that regulates cells with ESC characteristics. ESC-like cells are influenced by the Ras/BRAF/MEK/ERK1/2 and PI3KCA/AKT/mTOR pathways, which directly regulate cellular proliferation and stemness, and interact with the RAS at multiple points. Gain-of-function mutations affecting these pathways have been identified in many types of cancer and VAs, that have been treated with targeted therapies with some success. In cancer, the RAS promotes tumor progression, treatment resistance, recurrence, and metastasis. The RAS modulates cellular invasion, migration, proliferation, and angiogenesis. It also indirectly regulates ESC-like cells via its direct influence on the tissue microenvironment and by its interaction with the immune system. In vitro studies show that RAS inhibition suppresses the hallmarks of cancer in different experimental models. Numerous epidemiological studies show a reduced incidence of cancer and improved survival outcomes in patients on RAS inhibitors, although some studies have shown no such effect. The discovery of ESC-like cells that express RAS components in infantile hemangioma (IH) underscores the paradigm shift in the understanding of its accelerated involution induced by β-blockers and angiotensin-converting enzyme inhibitors. The findings of SOX18 inhibition by R-propranolol suggests the possibility of targeting ESC-like cells in IH without β-blockade, and its associated side effects. This article provides an overview of the current knowledge of ESC-like cells and the RAS in VAs, cancer, and fibroproliferative conditions. It also highlights new lines of research and potential novel therapeutic approaches for these unsolved problems in plastic surgery, by targeting the ESC-like cells through manipulation of the RAS, its bypass loops and converging pathways using existing low-cost, commonly available, safe oral medications.